Full Gauge-Parameter-Independent Higgs-Boson Self-Energy - Kniehl, Bernd; Palisoc, Caesar (Science Diliman: A Journal of Pure and Applied Sciences; Vol 12 No 1 (2000), 2007)
We calculate the self-energy of the standard-model Higgs boson by means of the pinch technique. We work in the general Rξ gauge and show that the final result is independent of the gauge parameters. This result is useful in order to demonstrate that the threshold singularities encountered in the description of Higgs-boson production and decay in the on-shell renormalization scheme only arise at physical thresholds and are independent of the chosen gauge.
Keywords: SM Higgs-boson self-energy, pinch technique, S-matrix PT framework, gauge invariance, quantum corrections, perturbation theory